2018
DOI: 10.1002/slct.201801060
|View full text |Cite
|
Sign up to set email alerts
|

Pd/SBA‐15 Catalysts for Hydrogenation of Furfuryl Alcohol to Tetrahydrofurfuryl Alcohol

Abstract: With the aim of hydrogenating furfuryl alcohol into tetrahydrofurfuryl alcohol by avoiding high pressure operations and harmful solvents, a mild and sustainabable operaration is adopted. At this juncture, 1Pd/SBA15, 2Pd/SBA‐15 and 3Pd/SBA‐15 catalysts (where 1, 2 and 3 are wt% of Pd) were prepared by wet impregnation method and characterized by powder X‐ray Diffraction, N2‐physorption, Scanning Electron Microscopy, Transmission Electron Microscopy, CO‐Pulse Chemisorption, H2‐Temperature Programmed Reduction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…supports. The H2-TPR profiles of the Pd/SBA as well as the materials containing 5 and 20 % of Al revealed the presence of two peaks at low temperatures which corresponds to the reduction of palladium oxide particles [49,50]. It is well known that PdO reduces easily at low temperatures (below 200 °C) [11,16,20,[49][50][51].…”
Section: Catalyst Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…supports. The H2-TPR profiles of the Pd/SBA as well as the materials containing 5 and 20 % of Al revealed the presence of two peaks at low temperatures which corresponds to the reduction of palladium oxide particles [49,50]. It is well known that PdO reduces easily at low temperatures (below 200 °C) [11,16,20,[49][50][51].…”
Section: Catalyst Characterizationmentioning
confidence: 96%
“…The H2-TPR profiles of the Pd/SBA as well as the materials containing 5 and 20 % of Al revealed the presence of two peaks at low temperatures which corresponds to the reduction of palladium oxide particles [49,50]. It is well known that PdO reduces easily at low temperatures (below 200 °C) [11,16,20,[49][50][51]. The H2 consumption at lower temperature (70-73 °C) is associated with the reduction of PdO outside of the pores, and the one at higher temperature (88-92 °C) is due to the reduction of PdO inside the pores.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Chada et al obtained 85 C % selectivity of THFA from furfuryl alcohol over the Pd/SBA-15 catalyst. 17 Wang et al reported the Pt/CeO 2 catalyst with a special crystal plane of (100) for efficient hydrogenolysis of furfuryl alcohol into 1,2-PeD. 18 Amada et al reported the direct transformation of furfural to 1,2-PeD (73 C%) using a Pt/HT nanoparticle catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Chada et al. obtained 85 C% selectivity of THFA from furfuryl alcohol over the Pd/SBA-15 catalyst . Wang et al reported the Pt/CeO 2 catalyst with a special crystal plane of (100) for efficient hydrogenolysis of furfuryl alcohol into 1,2-PeD .…”
Section: Introductionmentioning
confidence: 99%
“…7 d Other studies on FAL hydrogenation over Pd/SiO 2 also showed that Pd NPs on SiO 2 were very selective toward the hydrogenation of furan ring. 8 On the other hand, some reports have found that Pd/SiO 2 was an excellent catalyst for the reductive etherification of C O bond in aldehydes like cyclohexanone and etc. 9 We speculate that the introduction of Na during the catalyst preparation may have a profound role in this process.…”
Section: Introductionmentioning
confidence: 99%